Penetrating Crohn Disease Is Not Associated With a Higher Risk of Recurrence After Surgery: A Prospective Nationwide Cohort Conducted by the Getaid Chirurgie Group. Issue 5 (November 2019) - Maggiori, Léon; Brouquet, Antoine; Zerbib, Philippe; Lefevre, Jérémie H.; Denost, Quentin; Germain, Adeline; Cotte, Eddy; Beyer-Berjot, Laura; Munoz-Bongrand, Nicolas; Desfourneaux, Véronique; Rahili, Amine; Duffas, Jean-Pierre; et al.
Abstract : Objective: The aim of this study was to assess recurrence risk factors following ileocolonic resection (ICR) for Crohn disease (CD) in a nationwide cohort study Summary Background Data: Recurrence rate after ICR for CD can be up to 60%, but its predictive factors have never been evaluated in large prospective cohort studies. Methods: From 2013 to 2015, 346 consecutive patients undergoing ICR for CD and a postoperative ileocoloscopy within 6 to 12 months after surgery at 19 academic French centers were included prospectively. Results: Twelve-month postoperative endoscopic (Rutgeerts score ≥i2) and clinical recurrence rates were 57.6% [95% confidence interval (CI), 54.2–61.0] and 11.3% (95% CI, 9–13.6), respectively. A total of 185 patients (54%) had a postoperative CD prophylaxis, comprising thiopurine in 69 (20%), or anti-tumor necrosis factor (TNF) therapy in 93 (27%). In multivariate Cox regression analysis, absence of postoperative smoking odds ratio [OR] = 0.60 (95% CI, 0.40–0.91); P = 0.016, postoperative prophylaxis [OR = 0.60 (95% CI, 0.41–0.88); P = 0.009], and penetrating disease behavior [OR = 0.58 (95% CI, 0.39–0.86); P = 0.007] were the only independent predictors of reduced endoscopic recurrence risk. Postoperative prophylaxis [OR 0.31 (95% CI, 0.15–0.66); P = 0.002), and penetrating behavior [OR = 00.36 (95% CI, 0.16–0.81); P = 0.013), were the only independent predictors of reduced clinical recurrence risk. Postoperative anti-TNF therapy was associated with a significant reduction of both 12-month risks of endoscopic ( P < 0.001) and clinical ( P = 0.019) recurrences. Conclusion: Absence of postoperative smoking, CD prophylaxis, and penetrating disease behavior could be independent predictors of reduced postoperative recurrence after ICR for CD. Prophylactic anti-TNF therapy reduces both endoscopic and clinical recurrence rates. It suggests that upfront surgery followed by postoperative anti-TNF therapy is probably the best therapeutic approach for complex CD (penetrating disease behavior).